Parallel magnetotransport in multiple quantum well structures - Sheregii, E.M.; Ploch, D.; Marchewka, M.; Tomaka, G.; Kolek, A.; Stadler, A.; Mleczko, K.; Strupiński, W.; Jasik, A.; Jakiela, R. (Физика низких температур, 2004)
The results of investigations of parallel magnetotransport in AlGaAs/GaAs and
InGaAs/InAlAs/InP multiple quantum wells structures (MQW’s) are presented in this paper.
The MQW’s were obtained by metalorganic vapour phase epitaxy with different shapes of QW,
numbers of QW and levels of doping. The magnetotransport measurements were performed in wide
region of temperatures (0.5–300 K) and at high magnetic fields up to 30 T (B is perpendicular and
current is parallel to the plane of the QW). Three types of observed effects are analyzed: quantum
Hall effect and Shubnikov—de Haas oscillations at low temperatures (0.5–6 K) as well as
magnetophonon resonance at higher temperatures (77–300 K).